A new silicon phthalocyanine dye induces pyroptosis in prostate cancer cells during photoimmunotherapy - Wolf, Isis; Storz, Jonas; Schultze-Seemann, Susanne; Esser, Philipp R.; Martin, Stefan F.; Lauw, Susan; Fischer, Peer; Peschers, Marie; Melchinger, Wolfgang; Zeiser, Robert; Gorka, Oliver; Groß, Olaf; et al. (Bioactive materials, 2024)
Photoimmunotherapy (PIT) combines the specificity of antibodies with the cytotoxicity of light activatable photosensitizers (PS) and is a promising new cancer therapy. We designed and synthesized, in a highly convergent manner, the silicon phthalocyanine dye WB692-CB2, which is novel for being the first light-activatable PS that can be directly conjugated via a maleimide linker to cysteines. In the present study we conjugated WB692-CB2 to a humanized antibody with engineered cysteines in the heavy chains that specifically targets the prostate-specific membrane antigen (PSMA). The resulting antibody dye conjugate revealed high affinity and specificity towards PSMA-expressing prostate cancer cells and induced cell death after irradiation with red light. Treated cells exhibited morphological characteristics associated with pyroptosis. Mechanistic studies revealed the generation of reactive oxygen species, triggering a cascade of intracellular events involving lipid peroxidation, caspase-1 activation, gasdermin D cleavage and membrane rupture followed by release of pro-inflammatory cellular contents. In first in vivo experiments, PIT with our antibody dye conjugate led to a significant reduction of tumor growth and enhanced overall survival in mice bearing subcutaneous prostate tumor xenografts. Our study highlights the future potential of the new phthalocyanine dye WB692-CB2 as PS for the fluorescence-based detection and PIT of cancer, including local prostate tumor lesions, and systemic activation of anti-tumor immune responses by the induction of pyroptosis.